Rancang Bangun Alat Ukur Tekanan Hidrostatis dan Kedalaman Perairan Berbasis Sensor Serat Optik - Yunus, M Fachri; Harmadi, Harmadi (Jurnal Fisika Unand, 2024)
The design of hydrostatic pressure and water depth measuring instrument based on optical fiber sensor using intrinsic method has been carried out. The design of this hydrostatic pressure and water depth measuring instrument consists of fiber optic sensors which include a light source in the form of a 5V diode laser, FD-620-10 optical fiber as a light transmission medium and OPT101 photodetector. Arduino Uno R3 board as a data processor, and I2C LCD as a viewer of measurement results. Characterization of the fiber optic sensor is done by varying the bending based on the number of serrations that cause differences in output voltage on the fiber optic sensor. Optimal results were obtained when the serrations amounted to 5 with a sensitivity value of -0.0863 V/kPa. The maximum hydrostatic pressure that can be measured is at a water depth of 1.5 m. The measurement results of hydrostatic pressure and water depth obtained with the designed tool against the theory and comparison tool obtained a percentage error of 4.42% and 4.32%, respectively